Green Methodology for Learning Assessment. (2016) - Moldovan, Liviu; Moldovan, Ana-Maria
Abstract: In this paper a pear learning approach is proposed to help trainees learn from peers and make reflections in vocational education and training (VET) by using mobile devices. Finally it is created a green learning arena by employment of peer assessment, a new methodological approach in 5 steps. It is used the free available software Google Form. To evaluate the effectiveness of the proposed approach, an experiment was conducted in an environmental management course. A total of 48 trainees participating in the experiment were assigned to an experimental group and a control group. The trainees in the experimental group learned with the peer assessment, while those in the control group learned with the conventional approach. It was found from the experimental results that the proposed interactive approach significantly improved the trainees' learning motivation and learning achievements.